Perancangan Sistem Pencatatan Akuntansi Pada Toko La Collection - Robby Krisyadi; Laurence Laurence (Universitas Internasional Batam, 2021)
LA Collection Store is a fashion store located in the Penuin Market Area, Batam. The purpose of this student creativity program is to improve the financial recording system at the LA Collection Store into a system that can facilitate business owners from preparing an accurate business financial reports in accordance with applicable accounting standards. Currently, LA Collection Store record transactions manually, resulting in inaccurate reports. Therefore, the author will design a computerized accounting recording system using Microsoft Access application to assist LA Collection Store in preparing financial reports. The financial reports produced by the accounting recording system are expected to be taken into consideration by business owners in making business decisions. The author designed an accounting recording system based on requirement from LA Collection Store’s business owner. The result of the designed system are sales form, purchase form, transaction form, inventory form, fixed asset form, account form, statement of financial position, income statement, statement of change in equity, statement of cash flow, general journal, general ledger, inventory report, remaining inventory report, and fixed assets report. Following the authors carry out the implementation process and ensure the designed system can be run without a hitch, the author hand over the accounting recording system to business owners. Microsoft Access system that has been designed is expected to be able to solve the problems faced by LA Collection Stores. Recommendations that can be taken into consideration for the next implementation of student creativity program is to design a more comprehensive accounting recording system that can produce more types of reports such as budget reports and dead stock reports. In addition, the next implementation of student creativity program can also try to design a web-based or online accounting recording system so that users can access the system flexibly.